Developing Reading and Listening Skills of an Inclusion Student: An Action Research - Fatih Çetin Çetinkaya; Mücahit Durmaz; Abdurrahman Baki Topçam; Muhammet Sönmez (Sakarya University Journal of Education)
Inclusion students, like all students, need to develop strong reading and listening skills to communicate effectively, understand instructions, and retain information. These skills are also important for their independence and future career success. Improving these skills can help inclusion students to achieve their academic, social, and professional goals. The main purpose of this research is to improve the reading and listening skills of an inclusion student studying at the 2nd grade level. For this purpose, the study was designed and conducted as an action research. First of all, the current level of the student in reading and listening skills was determined. Interactive reading and repeated reading methods were used in the intervention process. The intervention process of the study lasted for 6 weeks. In this process, 14 different children's picture books were read by the student's parents using the interactive reading method. Then, the student was allowed to read children's picture books until he reached the level of free reader. As a result of the research, it was concluded that the student made fewer reading errors than before the intervention process, the rate of word recognition and the reading prosody score increased, and the success of reading comprehension and listening comprehension improved.